PERAN AGAMA DALAM MENCIPTAKAN STEREOTIPE MASYARAKAT (STUDI KASUS LAKI-LAKI YANG BERAMBUT PANJANG DI DUSUN SUNTALANGU) - Sy, A. Irman Maulana; Subaidi, Subaidi (Universitas Cokroaminoto Yogyakarta, 2023)
Humans are social creatures who live side by side. Society consists of individuals with diverse characters and visions of life. The diversity of character and vision of each individual makes it vulnerable to create conflict. Therefore, these individuals create groups in order to survive in social life. A group generally has the same vision or views regarding various problems, both formal and material. The aim is to strengthen ties between one another, thereby creating harmony within the group. However, on the other hand, the formation of a group indicates that there is another group which had fewer members, would become a minority. People with long hair are an example of a minority in Suntalangu, East Lombok Regency. The community group in this hamlet really adheres to the values ​​taught in the Islamic religion in implementing them in social life. However, in practice, these community groups often have a narrow view, thereby eliminating the values ​​of inclusiveness in viewing a problem. This research is qualitative with a case study approach. This research aims to determine the role of religion in creating societal stereotypes of men with long hair in Suntalangu, East Lombok Regency. By knowing the role of religion in creating societal stereotypes, it is hoped that we can increase inclusiveness between individuals in social life.